THE CONFINEMENT OF WOMEN AS A PRACTICE. THE EXAMPLE OF CÓRDOBA, ARGENTINA, IN THE CONTEXT OF LATIN AMERICA IN THE EIGHTEENTH AND NINETEENTH CENTURIES - Ghirardi, Mónica; Vassallo, Jaqueline (Revista de Historia Social y de las Mentalidades, 2011)
In this work we will try to analyze the practice of the feminine, judicial and domestic confinement, purposes and uses. From documentary primary sources (diaries of visit of the jail to come to terms; books of revenue to the orphans’ college; lawsuits of nullities and separation of bodies; judicial processes) explore forms of control of the feminine body across the figure of the judicial “deposit” used by the secular and the ecclesiastic justice, domestic, judicial encirclements, colleges and convents of the city of Cordova during the XVIIIth century and the first half ofthe XIXth.
Keywords: gender; feminine confinement; women; social discipline